8-3(x-1)=3+x

Simple and best practice solution for 8-3(x-1)=3+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-3(x-1)=3+x equation:



8-3(x-1)=3+x
We move all terms to the left:
8-3(x-1)-(3+x)=0
We add all the numbers together, and all the variables
-3(x-1)-(x+3)+8=0
We multiply parentheses
-3x-(x+3)+3+8=0
We get rid of parentheses
-3x-x-3+3+8=0
We add all the numbers together, and all the variables
-4x+8=0
We move all terms containing x to the left, all other terms to the right
-4x=-8
x=-8/-4
x=+2

See similar equations:

| (x-5)/9=-3 | | -u/4=-45 | | 6(w–97)=-36 | | (10x-5)-(3x+2)=75 | | 75=3x+4x-9 | | 5x+12-7x=-3(5x+8) | | 5m-10=275 | | 3x+17x-7=4(5x+7) | | -15+7+17y=2y+70 | | 12x+11=27 | | 1/2(x+4)-11/2X=-5 | | -8t+9=-5t–10–8 | | -9+x/8=-4x-8/7 | | 19x-7=12x-28 | | -10+7b+5=-5+9b | | (x/2)+(5/5)=2x/3 | | 2m+4/8=m | | 102/3=r+121/6 | | (14x+1)+(5x-7)=89 | | 65x-15-9x=11+56x-26 | | -4(5-7x)-(1-x)=4(x-3) | | 2x+65+25=x | | .8x+1.6x-3.2=-12.8 | | 1.5p=1.2(p+6.4) | | 3(2x+7)=14x+5-8x+16 | | -5=1/2(x | | 2x2-54=12x | | -9=-5x+4x-5 | | a-32+55a=a(2a-8)-a2+39 | | 3x+15-10x-16=3x-x-17 | | 3/2x=4/x+1/4 | | 1–m=6–6m |

Equations solver categories